Synergy of metal and nonmetal dopants for visible-light photocatalysis: a case-study of Sn and N co-doped TiO2. Issue 14 (21st March 2016) - Zhuang, Huaqiang; Zhang, Yingguang; Chu, Zhenwei; Long, Jinlin; An, Xiaohan; Zhang, Hongwen; Lin, Huaxiang; Zhang, Zizhong; Wang, Xuxu
Abstract : The co-incorporation of Sn and N dopants results in an obvious synergistic effect in the Sn and N co-doped TiO2 sample, which can remarkably enhance the photocatalytic performances of TiO2 sample. Abstract : This paper mainly focuses on the synergistic effect of Sn and N dopants to enhance the photocatalytic performance of anatase TiO2 under visible light or simulated solar light irradiation. The Sn and N co-doped TiO2 (SNT- x ) photocatalysts were successfully prepared by the facile sol–gel method and the post-nitridation route in the temperature range of 400–550 °C. All the as-prepared samples were characterized in detail by X-ray diffraction, UV-vis diffuse reflectance spectroscopy, transmission electron microscopy, X-ray photoelectron and electron spin resonance spectroscopy and photoelectrochemical measurements. The characterization results reveal that the co-incorporation of Sn and N atoms remarkably modifies the electronic structure of TiO2, which gives rise to a prominent separation of photogenerated charge carriers and more efficient interfacial charge-transfer reactions in a photocatalytic process. The enhanced photocatalytic activity is attributed to the intensified active oxygen species including hydroxyl radicals (˙OH) and superoxide anion radicals (O2 ˙ − ) for degradation of organic pollutants. And the result of photocatalytic hydrogen production further confirms the existence of the synergistic effect in the SNT- x samples, because they exhibit higher photocatalytic activity than the sum of N/TiO2 and Sn/TiO2 . This work provides a paradigm to consolidate the understanding of the synergistic effect of metal and non-metal co-doped TiO2 in domains of photocatalysis and photoelectrochemistry.